My experience as a host at La Cevicheria restaurants (2023)
The following report provides a comprehensive overview of La Cevicheria, a restaurant located in Cartagena, focusing on various aspects such as its background, organizational structure, mission, values, and operational challenges. The information presented in this report is based on my experience in the restaurant la Cevicheria. It is important to mention that this report is written for academic purposes. The report starts with a contextual approach, describing La Cevicheria clientele, location, and physical setting. It highlights the target market and the ways in which the restaurant reaches its customers. The organizational structure is then outlined, detailing the roles and responsibilities of key positions within the restaurant, including the owner, management team, front-of-house staff, and back-of-house staff. Further sections delve into the intangible aspects, such as its culture, work ethic, morale, and general staff interaction. The environment is analyzed, discussing whether it leans towards a professional or informal atmosphere and how it impacts staff and customer interactions. Additionally, the report examines the challenges faced by La Cevicheria on a daily basis or on a larger scale, including issues related to the physical space, resources, clientele, and industry dynamics. The report concludes by addressing specific tasks and objectives of the host role, highlighting the challenges faced during this time, and identifying strengths and weaknesses as an employee. It suggests meaningful and realistic solutions to address the identified problem, emphasizing the importance of effective communication, process optimization, employee engagement, resource management, and continuous improvement. It is important to note that although the information presented in this report is based on general knowledge and understanding, it should be considered in the context of an academic exercise, as it is made using analytical tools learned during the semester and thus provides ideas and recommendations that can be further explored in a practical setting.